Unveiling the Significance of Proposing Hibah as an Alternative to Nafkah Security for Widows - Amylia Fuziana Azmi; Nor Laila Ahmad; Mohamad Zaharuddin Zakaria; Nik Salida Suhaila Nik Saleh; Mushaddad Hasbullah (USIM Press, 2024)
Malaysian Journal of Syariah and Law Vol. 12, No. 2, pp. 529-534